MEASUREMENT OF REGIONAL GOVERNMENT FINANCIAL PERFORMANCE IN INDONESIA - REDIYANTO PUTRA; RAHMA RINA WIJAYANTI; ORYZA ARDHIARISCA (Jurnal Bisnis dan Akuntansi, 2020)
This study aims to determine the financial performance of all local governments in Indonesia. This study uses financial data from all the districts/cities and provinces in Indonesia from 2013 to 2015. The data collection techniques used in this study is documentation. This research used descriptive and quantitative analysis methods. The results of the study show that the government's financial performance in Indonesia has been effective but inefficient. This is evident from the ratio of the financial effectiveness ratio of local governments in Indonesia in 2013-2015 in the range of 102-121%, but the ratio of financial efficiency of local governments in Indonesia in 2013 to 2015 was in the range of 99% -104%. Financial performance that is not optimal from this local government is because during 2013-2015 the contribution of taxes and regional retribution on Regional Original Income was low so that in the end it caused the level of income received by the regional government to be not too large